Glucocorticoid Receptor‐Binding and Transcriptome Signature in Cardiomyocytes. Issue 6 (19th March 2019) - Severinova, Elena; Alikunju, Saleena; Deng, Wei; Dhawan, Puneet; Sayed, Nazish; Sayed, Danish
Abstract : Background: An increase in serum cortisol has been identified as a risk factor for cardiac failure, which highlights the impact of glucocorticoid signaling in cardiomyocytes and its influence in the progression of failure. Dexamethasone, a synthetic glucocorticoid, is sufficient for induction of cardiomyocyte hypertrophy, but little is known of the glucocorticoid receptor (GR) genome‐binding and ‐dependent transcriptional changes that mediate this phenotype. Methods and Results: In this study using high‐resolution sequencing, we identified genomic targets of GR and associated change in the transcriptome after 1 and 24 hours of dexamethasone treatment. We showed that GR associates with 6482 genes in the cardiac genome, with differential regulation of 738 genes. Interestingly, alignment of the chromatin immunoprecipitation and RNA sequencing data show that, after 1 hour, 69% of differentially regulated genes are associated with GR and identify as regulators of RNA pol II–dependent transcription. Conversely, after 24 hours only 45% of regulated genes are associated with GR and involved in dilated and hypertrophic cardiomyopathies as well as other growth‐related pathways. In addition, our data also reveal that a majority of genes (76.42%) associated with GR show incremental changes in transcript abundance and are genes involved in basic cellular processes that might be regulated by the dynamics of promoter‐paused RNA pol II, as seen in hearts undergoing hypertrophy. In vivo administration of dexamethasone resulted in similar changes in the cardiac transcriptome, as seen in isolated cardiomyocytes. Conclusions: Our data reveal genome‐wide GR binding sites in cardiomyocytes, identify novel targets and GR‐dependent change in the transcriptome that induces and contributes to cardiomyocyte hypertrophy.